Clinical Performance of Toris K Contact Lens in Patients with Moderate to Advanced Keratoconus: A Real Life Retrospective Analysis - Ihsan Yilmaz; Ferah Ozcelik; Berna Basarir; Gokhan Demir; Gonul Durusoy; Muhittin Taskapili (Journal of Ophthalmology)
Objectives. To evaluate the visual performance of Toris K soft contact lenses in patients with moderate-to-advanced keratoconus and also to compare the results according to cone types, cone location, and severity of keratoconus. Materials and Methods. Sixty eyes of 40 participants were included in this retrospective study. Uncorrected visual acuity (UCVA), best-spectacle corrected visual acuity (BCVA), best-contact lens corrected visual acuity (BCLCVA), and comfort rating via visual analogue scales (VAS) were measured. Results. The mean age was 27.3 ± 8.6 years (range: 18 to 54). The mean logMAR UCVA, BCVA, and BCLCVA were 0.85 ± 0.38 (range: 0.30–1.30), 0.47 ± 0.27 (range: 0.10–1.30), and 0.16 ± 0.20 (range: 0–1.00). There were significant increases in visual acuities with contact lenses (p<.05). BCLCVA was significantly better in oval type than globus type (p=.022). UCVA and BCLCVA were significantly better in moderate keratoconus group (p=.015, p=.018). The mean line gain in Snellen was 3.6 ± 1.8 lines (range: 0–7 lines). The mean line gain was higher in central cone group than paracentral cone group and oval group than globus group (p=.014, p=.045). The mean VAS score was 8.14 ± 1.88 (range: 6–10). Conclusions. Toris K can improve visual acuity of patients with keratoconus. Toris K is successful even in the moderate and advanced form of the disease.